System do zdalnego monitorowania stanu wału przeciwpowodziowego nad Odrą = Remote Odra river flood embankment state monitoring system - Macioszek, Łukasz; Łukaniszyn, Norbert; Rybski, Ryszard; Kostecki, Jakub; Kołodziejczyk, Urszula; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents the architecture of proposed measurement system for collecting and presenting current information on the flood embankment condition. The system periodically collects data from sensors connected to the data logger, which are finally sent to the server.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne